Measuring the indirect costs and benefits of greenhouse gas mitigation options: Methodology and a case study from Hungary - Alistair Hunt; Pamela Mason; Anil Markandya (Fondazione Eni Enrico Mattei (FEEM), 1999)
This paper considers the problem of how a government, having decided to reduce greenhouse gas emissions, identifies the policy or mix of policies that achieves this reduction at the lowest possible net economic cost. This involves accounting for the fact that each potential policy for reducing GHGs has a different financial cost, and implies a different set of direct and indirect costs and benefits, each of which must be weighted according to the government's particular priorities. This paper reports on work that extends the existing analysis of the costs and benefits implied by different mitigation policies to include employment and income distribution effects, reduced air pollution and the achievement of environmental and economic sustainability. We outline an approach for compiling these elements into selection criteria that will help policymakers identify the lowest-cost mitigation policies. We present an application of the methodology to a prospective energy-saving project in Hungary. We argue that this methodology, although by no means precise at this stage, provides a useful decision-making tool.
Keywords: H40; Q28; Q48; 330; Climate change; mitigation; net costs; non-monetary; health; employment; pollution; sustainability; Klimaschutz; Energieeinsparung; Kosten; Ungarn